Development of an Intuitive Link Budget Tool for military satellite communications - Zhiger, Stambakiyev (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Nowadays, the military needs to send and receive high quality videos, audios and pictures despite the all-year-around rain occurrences experienced by tropical countries including Malaysia. When it rains, military troops are then expected to adjust accordingly different parameters of their satellite communication (satcom) equipment. Military forces are expected to be highly mobile in all conditions regardless of time, location and weather. In a tropical environment such as Malaysia, where rain occurs almost all year around and in most instances, the rainfall rate is much higher when compared to temperate regions, it is therefore critical to calculate correlation of several factors, such as receiver sensitivity, bandwidth, transmit power, antenna gain and all losses. Military forces are not fixed in only one location. Today a troop might be settled in Taman Negara, Pahang; tomorrow in the jungles of Terengganu and within the next weeks perhaps the platoon could be sent to East Malaysia. Satellite communication equipment are strategic asset and very likely not fixed at only specific locations. They might have been hauled by the military forces from places to places from time to time. Satcom equipment might be carried by one soldier, as well as installed on the rooftop of a military truck depending on the size and measure. Taking into account all facts above, it is therefore essential to develop an Intuitive Link Budget Tool or Tool that incorporates elements of climate conditions, displacement to at specific region at a specified time of soldiers, as well as military trucks. Considering every previously mentioned certainty, it is without a doubt, critical to develop an intelligent real-time link budget tool. An Intuitive Link Budget Tool (ILB-T) that assimilates components namely atmosphere conditions and the troop's locality had been proposed and developed during the study. The proposed ILB-T for military satellite communication was developed using HTML, PHP, Javascript, and MySQL. The performance of the proposed ILB-T was also evaluated for the desired carrier over noise (C/N) ratio using rainfall rate, predicted attenuation over rainfall rate, and specific attenuation based on the rainfall rate. The acquired results suggest that the proposed ILB-T is more efficient in terms of real-time link budgeting compared to that of previously proposed methods.